Revitalisasi Filsafat Kebahagiaan Buya Hamka sebagai Respon terhadap Fenomena Mental Distress di indonesia (EL-FIKR: Jurnal Aqidah dan Filsafat Islam, 2023)
Ideally normal humans have the thought search for happiness. However, in Indonesia still show that phenomena of mental distress. Therefore, to get happiness, one must try to know the nature of happiness itself. This paper aims to describe: (1) The essence of happiness according to Hamka's thought; (2) The elements of happiness in Hamka's perspective; and (3) the relevance of the concept of happiness according to Hamka in the present context. This paper uses a qualitative approach in exploring the data. The content analysis approach is used to explore Hamka's thoughts on the philosophy of happiness. The primary data is taken from Hamka's book entitled: â€œTasawuf Modern: Bahagia Itu Dekat dengan Kita, Ada di dalam Diri Kita.â€ While secondary data is taken from other relevant literature. The results of this study are: (1) According to Hamka, the essence of happiness is divided into three levels, namely: happiness in the afterlife, happiness of the mind, and happiness of the body. (2) The elements that make up human happiness are having: mindset, iâ€™tikad, belief, faith, religion. (3) Hamka's thoughts about philosophy of happiness are still very relevant for overcoming mental distress in society. Keywords: Philosophy, Happiness, Hamka, Mental Distress.